Protestanti u službi Petrovaradinske pukovnije u drugoj polovici 18. stoljeća - Nujić, Pavao (2019)
Autor u radu analizira prisutnost protestanata u službi Petrovaradinske pukovnije na temelju službenih pukovnijskih serijalnih izvora i tri cjelovita popisa pukovnije iz 1767., 1772. i 1792. godine. Protestanti su promatrani iz perspektive aktivne vojne službe kao istaknuti pojedinci unutar časničkoga kadra i kao vjerska skupina i manjina među običnim krajišnicima. Prikazano je stabilno postojanje protestantskoga elementa na svim razinama pukovnijske službe kroz promatrana desetljeća 18. stoljeća, a što je predstavljalo posebnost Petrovaradinske pukovnije u odnosu na ostale pukovnije Slavonske i Hrvatske vojne krajine toga razdoblja.
The area of the Croatian and Slavonian Military Border the 18th century was inhabited by a Catholic and Orthodox population from which Grenzers were recruited, while other religious groups were severely limited in that regard. Protestants were present mostly only within the officer staff of certain regiments and they came from other parts of the Monarchy or even other countries as professionals and only stayed temporarily while their service lasted. In this regard, the Petrovaradin Regiment was not an exception and the arrival of Protestant officers can be traced back to 1767 in the documents and muster rolls of the regiment. A special case was the permanent inhabitation of Protestant families in the area of the Regiment, from which ordinary Grenzers were recruited. Their presence in the service was first noted in a muster roll from 1772 and, from then, can be continuously traced to all levels of the Regiment. The Petrovaradin regiment, therefore, had a steady Protestant minority in its composition throughout the final three decades of the 18th century, which was not common for Military Border.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 320-322.
Sažetak ; Summary.
Keywords: Vojna služba -- Protestanti -- Krajišnici; Petrovaradinska pukovnija; 18. st; Vojna krajina -- Srijem